15 years of research on wastewater treatment high rate algal ponds in New Zealand: discoveries and future directions. Issue 4 (1st October 2020) - Sutherland, Donna L.; Ralph, Peter J.
ABSTRACT: Over the last 15 years, New Zealand led research on wastewater treatment high rate algal ponds (HRAP) has focused on ways to optimise pond performance, particularly with respect to nutrient removal and resource recovery (microalgal biomass production). The primary motivation for most of this research has been the need to cost-effectively improve wastewater treatment, particularly in small towns and rural communities, where wastewater treatment would otherwise be unaffordable. The ability to recover resources (water and nutrients) helps enable a circular bio-economy, through the reuse of these recovered resources in future products. New Zealand HRAP research has focused on 10 broad categories, including improving pond performance (nutrient removal and biomass yield), environmental impacts of HRAPs, pond design and operation, microalgal and zooplankton community composition and control, algal-based products, enhancing phosphorus removal, biomass harvesting and emerging contaminants. Research has been carried out at a range of scales, including mesocosm, pilot-scale and full-scale. Simple modification to how HRAPs are operated, such as culture depth, operating ponds in series, biomass recycling and night-time CO2 addition, have been shown to improve pond performance, particularly nutrient removal, biomass productivity, species dominance maintenance or zooplankton graze control. However, despite our improved understandings over the last 15 years, there are still a number of priorities for increasing HRAP performance, including effective CO2 addition at full-scale, improving phosphorus removal and reducing potential environmental impacts of HRAPs. Uptake of HRAP technology by local government bodies and industries is low and the reasons for this are not fully clear. Cost-effective and sustainable harvesting of the microalgal/bacterial biomass, to ensure effluent discharge meets total nutrient and total suspended solids load limits, is one barrier that must be overcome to allow greater uptake of this technology.